Manejo outonal de Conyza spp. baseado em glyphosate + 2,4-D, MSMA e amônio-glufosinato aplicados isoladamente ou em mistura com herbicidas residuais - Oliveira Neto, Antonio Mendes de (2011)
The of spread of Conyza ssp. in no-till areas of Parana is currently the biggest problem in weed control, especially during the off season time in fall/winter. With the aim of evaluating the effectiveness of different herbicide treatments applied in off season time on Conyza spp., four experiments were conducted after two corn harvest periods (June/July and July/August) in Campina da Lagoa and Floresta. For the first experimental period treatments consisted of glyphosate + 2.4-D (960 + 536 g ha-1), MSMA (2370 g ha-1), and glufosinate (400 g ha-1) isolated and associated with the residual herbicides metsulfuron-methyl (3.6 g ha-1), chlorimuron-ethyl (20 g ha-1), diclosulam (33.6 g ha-1), imazethapyr (100 g ha-1), imazaquin (180 g ha-1), flumioxazin (125 g ha-1), metribuzin (480 g ha-1), amicarbazone (420 g ha-1), isoxaflutole (56.25 g ha-1), and a non treated check. In the second experimental period glyphosate alone was added at 960 g ha-1. All applications were performed at postemergence of Conyza spp., which presented a maximum height of 2 and 12 cm for the first and the second experimental periods, respectively. The evaluations of effectiveness and residual control were performed until the pre-sowing soybean. The association of glyphosate + 2.4-D was efficient on burndown for all places studied. In the first experimental period residual activity was fundamental for fall management success, and diclosulam and chlorimuron-ethyl kept Conyza spp. plants in adequate stages to postemergence control until the pre-sowing of soybean in summer. In the second experimental period the association of glyphosate + 2.4-D with metsulfuronmethyl, chlorimuron-ethyl, diclosulam, imazethapyr, imazaquin, flumioxazin, metribuzin, amicarbazone, isoxaflutole, and MSMA + metsulfuron-methyl and MSMA + chlorimuron-ethyl, glufosinate + metsulfuron-methyl, glufosinate + chlorimuron-ethyl, glufosinate + diclosulam, glufosinate + metribuzin, and glufosinate + amicarbazone were efficient for fall management of Conyza spp.